Development of nanoparticles for targeted delivery of p38 MAPK inhibitor to myeloid dendritic cells - You, Jinge (2024)
Dendritic cells (DCs) are antigen-presenting cells which play an important role in the regulation of immune responses, and DC-based tumour immunotherapies have attracted much attention. Since one of the main routes of DC-mediated immunity is the identification and presentation of antigens to T-cells, historically most drug delivery systems have been designed to target DCs are for antigen delivery. However, in addition to the delivery of tumour-associated antigens, several small-molecule drugs have also been developed to activate DC antitumour immunity. BIRB0796 is a p38 MAPK inhibitor which our group has reported to activate human myeloid DCs (myDCs) function by upregulating IL-12 secretion and downregulating IL10 secretion. However, p38 MAPK is expressed ubiquitously, thus systemic treatment with BIRB0796 has led to undesired side effects and low drug efficacy. Moreover, since BIRB0796 is not very stable in solution, a formulation can probably protect BIRB0796 from degradation. Therefore, the aim of this PhD project is the preferential delivery of BIRB0796 to myDCs using carbohydrate-based nanoformulations able to exploit endocytic lectin receptors in immature DCs and elicit a range of anticancer responses. The work done in this PhD project has been divided into 3 chapters. In Chapter 3, we designed and synthesised a family of polymers (CHBn-b-ManAAm) by RAFT polymerisation, which can self-assemble into nanoparticles and encapsulate BIRB0796. CHBn-b-ManAAm nanoparticles were found to be selectively internalised by myDCs. Importantly, BIRB0796-loaded CHBn-b-ManAAm nanoparticles can activate myDCs – as estimated by the increasing of CD86 expression and IL-12 production - in a 10-fold lower dose compared with BIRB0796 as a free drug, suggesting that CHBn-b-ManAAm nanoparticles improve BIRB0796 uptake by myDCs. Having established the feasibility of carbohydrate-targeted delivery of BIRB07696 to DCs, in Chapter 4 we aimed to produce functionally analogous materials based on glycopeptides, possessing native proteinaceous backbones and natural glycosidic linkages, potentially more suitable for translational applications. Accordingly, here we developed a novel method for the rapid synthesis of glycopeptides, including the rapid synthesis of carbohydrate-based N-carboxyanhydrides (NCA) monomers and their rapid ring-opening polymerisation to give well-defined to glycopeptides. This enabled us to synthesise carbohydrate-based NCA monomers in < 10 min, synthesise homo glycopeptides up to DP= 80 within 10 h, synthesise co-peptides with 50% glycosylation up to DP=200 within 2 h and also synthesise carbohydrate-containing diblock peptides suitable for the assembly of nanoformulations. Mannose-based co-peptides synthesised with this method were selectively internalised by mannose receptor (CD206)-expressing cells, which indicates the potential of these peptides to be used for targeted drug delivery. In Chapter 5, we designed a family of glycosylated polypeptide copolymers through the NCA ROP method developed in Chapter 4 and we identified ((Man-Ser)30-r-Ala10)-b-Tyr20, which can self-assemble into nanoparticles and encapsulate BIRB0796 under aqueous conditions. ((Man-Ser)30-r-Ala10)-b-Tyr20 nanoparticles were selectively internalised by myDCs, and BIRB0796-loaded ((Man-Ser)30-r-Ala10)-b-Tyr20 nanoparticles were found to activate myDCs in a 100-fold lower dose compared with BIRB0796 as a free drug, which indicates that (((Man-Ser)30-r-Ala10)-b-Tyr20 nanoparticles improve BIRB0796 uptake by myDCs. Taken together, our results indicate that in this work we have developed polymeric nanoparticles for the delivery of BIRB0796 to myDCs. Since most delivery systems targeting dendritic cells were developed to deliver macromolecules, we potentially filled the gap in delivering small-molecule drug to DCs. Importantly, this technique can not only be used for BIRB0796, it can also be used to deliver other small-molecule modulators of DCs and further applied to, but not limited to, the therapeutics of tumour and autoimmune disease and DC imaging.